KONTRUKSI AKAD PENUKARAN UANG MENJELANG IDUL FITRI DALAM PERSPEKTIF FIKIH MUAMALAH - Nanda Shofi Maula; Abdul Khalid Ramadhan; Hamzah Surya Amaludin; Mohammad Saiful Rifai (JSE: Jurnal Sharia Economica, 2026)
The practice of money exchange before Eid al-Fitr has become a recurring socio-economic phenomenon in Indonesian society, especially through informal exchange services. The increasing public demand for small denomination banknotes has encouraged the growth of exchange services that charge additional fees. From the perspective of fiqh muamalah, this practice remains controversial because it involves the exchange of similar currency with different nominal values, raising concerns regarding contract clarity, transaction objects, and the potential existence of riba. This study aims to analyze the construction of contracts in pre-Eid money exchange practices and evaluate their conformity with the principles of Islamic commercial law. The research employed a qualitative descriptive method using empirical and normative approaches. Data were collected through interviews with three informal money exchange providers in Tulungagung and Blitar and two experts in fiqh muamalah and Islamic financial institutions. The study was strengthened through literature reviews of scientific journals, DSN-MUI fatwas, religious articles from NU and Muhammadiyah, and classical fiqh references. The findings show that legal differences arise from differing views regarding the object of the contract and the position of service fees. Clear separation between exchange transactions and service compensation is essential to ensure compliance with Islamic commercial principles properly.